The Exploitation-Exploration Dilemma of Fishing Vessels With Institutionally Protected Quota Shares - Hannevig, Hilde; Bertheussen, Bernt Arne (Frontiers in Marine Science, 2020)
It is an established “truth” in the literature that a company which restricts itself to utilize existing resources without exploring new business opportunities is doomed to fail in the long run. An underlying premise for the claim is that the competition arena is dynamic and organized according to free competition principles. This study, however, examines whether it is more profitable for a fishing vessel to primarily exploit existing resources when the quota shares of the players are institutionally protected so that there is no real competition between them. The context is Norwegian seagoing purse seiners, which in 2005 experienced the introduction of a more market oriented individual transferable quota (ITQ) system with some distinct modifications. The vessels in the study were classified into strategic groups based on their exploitation versus exploration approaches. Financial accounts covering the period 2003- 2017 were collected and analyzed to empirically address the issue. Some vessels did considerable explorative activities in the period studied by fishing related species, investing in quotas, and in new vessel technology. The findings suggest that firms which did not explore, but instead exploited their existing resource base performed relatively better than their peers except for EBITDA (earnings before interest, tax, depreciation and amortization) margin. Finally in the paper, the findings are discussed and implications outlined.